miR-155 is high-expressed in polycystic ovarian syndrome and promotes cell proliferation and migration through targeting PDCD4 in KGN cells - Huanjun Xia; Yaxian Zhao (Artificial Cells, Nanomedicine, and Biotechnology)
Polycystic ovarian syndrome (PCOS) is a typical disease of female endocrine and metabolic abnormalities. miR-155, famous as a multifunctional miRNA, promotes the proliferation, migration and invasion of human cancer cells. Therefore, we aimed to explore its regulation mechanism in PCOS. BrdU incorporation and apoptosis assay were used to test KGN cell survival. Luciferase activity experiment was employed to test targeting link between miR-155 and programmed cell death 4 (PDCD4). Migration and invasion assay were operated to examine the influence of miR-155 and PDCD4 in migration and invasion of KGN cells. In addition, quantitative reverse transcription-polymerase chain reaction (qRT-PCR) assay and western blot analysis were utilized to measure expression of miR-155 and other relative factors. We found that expression of miR-155 was high in PCOS patients’ tissues and it promoted proliferation, migration and invasion in KGN cells. Further studies found that PDCD4 was down-regulated by miR-155 and was a target of miR-155. Overexpression of PDCD4 promoted cell apoptosis to mitigate PCOS. Besides, up-regulation of PDCD4 suppressed PI3K/AKT and JNK signal pathways. To sum up, miR-155 promoted proliferation, migration, invasion and the activation of PI3K/AKT and JNK pathways in KGN cells through negatively regulating PDCD4.